Substructure (piling system) / Muhamad Amirul Adli Mohamad Azman - Mohamad Azman, Muhamad Amirul Adli (Universiti Teknologi MARA, Perak, 2014)
Substructure is very important for construction, therefore this report about the substructure in a building is based on the Uniform Building by Law (UBBL). This report was conducted on the building structure at Klinik Kesihatan Kuala Lumpur. The objective of this report is to learn and study about the function of the substructure and its requirements to make it suitable for the building. It will focus on the part of substructure that provides a suitable material for a typical building, such as single storey building or multi storey building. This report will also look at the criteria of the substructure to being choosen for a building.